Chang'E‐4 Rover Spectra Revealing Micro‐scale Surface Thermophysical Properties of the Moon. Issue 4 (23rd February 2021) - Wu, Yunzhao; Kührt, Ekkehard; Grott, Matthias; Jin, Qi; Xu, Tianyi; Helbert, Jörn; Hamm, Maximilian; Qin, Nannan; Ma, Jinsong; Vincent, Jean‐Baptiste; Hayne, Paul
Abstract: Lunar surface temperature variations provide key information about the thermophysical properties of the regolith. To date, temperatures have been measured using telescopes and orbiter instruments, providing information from mid‐infrared to long infrared (IR) wavelengths. Here, we report on temperature measurements in the short‐wavelength IR at centimeter scales observed in situ by the Chang'E‐4 rover. These local observations are an important complement to the existing large‐scale data. We show that even at 2.39 µm, where reflected radiation dominates the spectrum, thermal information can be retrieved from the data. The observed thermal radiances and derived temperatures depend on the observation geometry, specifically the relative azimuth angle between Sun and detector. This indicates that surface roughness on subresolution (millimeter) scales causes a non‐Lambertian radiation pattern of the emitted flux that is per definition independent of the observation angle. This behavior must be considered when deriving temperatures and thermal properties of lunar regolith. Plain Language Summary: The Chang'E‐4 spacecraft landed in the Von Kármán Crater in the Moon's South Pole‐Aitken Basin. A Visible and Near Infrared Spectrometer (VNIS) was carried on the "Yutu‐2" rover. The VNIS measured thermal emission on the surface of the Moon at short wavelengths and temperature variations at centimeter scales were retrieved during the first, second, and tenth day of rover operations on the lunar surface. These in situ observations are an important complement to the existing large‐scale measurements taken from orbit and reveal that the millimeter scale roughness plays an important role when deriving temperatures and physical properties of the lunar surface regolith. Key Points: The Chang'E‐4 VNIS observed the lunar surface in situ in the 0.45–2.4 μm wavelength range Emitted flux at centimeter scales is non‐Lambertian and depends on surface roughness and observation geometry Surface roughness as described by the bidirectional RMS slope was found to be 22°–24°